2006
DOI: 10.1071/ar05361
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nitrogen deficiency in wheat from spectral reflectance indices and basic crop eco-physiological concepts

Abstract: Abstract. We tested the capacity of several published multispectral indices to estimate the nitrogen nutrition of wheat canopies grown under different levels of water supply and plant density and derived a simple canopy reflectance index that is greatly independent of those factors. Planar domain geometry was used to account for mixed signals from the canopy and soil when the ground cover was low. A nitrogen stress index was developed, which adjusts shoot %N for plant biomass and area, thereby accounting for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(63 citation statements)
references
References 31 publications
1
58
1
3
Order By: Relevance
“…In the absence of other limiting factors, most literature has shown that ratios between red-edge and near-infrared reflectance provide the best correlation with leaf N concentration [35,37]. To detect N deficiency in wheat under different water status, a two-dimensional reflectance-based index combining an indicator of plant cover (NDVI), and an indicator of Chl content has been proposed [38]. However, in our study, a combination of two narrow-band indices did not improve yield prediction.…”
Section: Application To N Fertilizer Recommendationmentioning
confidence: 99%
“…In the absence of other limiting factors, most literature has shown that ratios between red-edge and near-infrared reflectance provide the best correlation with leaf N concentration [35,37]. To detect N deficiency in wheat under different water status, a two-dimensional reflectance-based index combining an indicator of plant cover (NDVI), and an indicator of Chl content has been proposed [38]. However, in our study, a combination of two narrow-band indices did not improve yield prediction.…”
Section: Application To N Fertilizer Recommendationmentioning
confidence: 99%
“…The Yellow band's ability to determine early PLS infestation can be attributed to its ability to identify "yellowness'', a common characteristic in diseased plants (Digital Globe, 2010;Oliveira et al, 2010 ). The Red-Edge band has the ability to assess plant nutrition, health and discriminate vegetation species (Filella and Peñuelas, 1994;Pinar and Curran, 1996;Daughtry et al, 2000;Rodriguez et al, 2006). According to Eitel et al (2011), the Red-Edge band can determine both the amount of chlorophyll and Nitrogen, the main determinants of the crop health.…”
Section: Discussionmentioning
confidence: 99%
“…NDRE was presented by Barnes et al (2000) to be used as a vegetation stress indicator with Canopy Chlorophyll Content Index (CCCI). NDRE is designed to respond to changes in chlorophyll concentration and nitrogen content (Rodriguez et al, 2006;Tilling et al, 2007). The equation of NDRE is:…”
Section: Estimation Methodsmentioning
confidence: 99%